2019
DOI: 10.1021/acs.est.8b04475
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Lead Solubility Potential of Untreated Groundwater of the United States

Abstract: In the U.S., about 44 million people rely on selfsupplied groundwater for drinking water. Because most selfsupplied homeowners do not treat their water to control corrosion, drinking water can be susceptible to lead (Pb) contamination from metal plumbing. To assess the types and locations of susceptible groundwater, a geochemical reaction model that included pure Pb minerals and solid solutions of calcite (Ca x Pb 1−x CO 3 ) and apatite [Ca x Pb 5-x (PO 4 ) 3 (OH; Cl; F)] was developed to estimate the lead sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
0
31
1
Order By: Relevance
“…Although the specific activation process and pre-treatment of the AC in the filter tested in this study is not known, the pH increased significantly in the effluent samples, with a greater increase at early time points (median influent pH at start-up of 5.23 compared to a median effluent pH at start-up of 9.13, p < 0.0005) and a gradual equilibration between the influent and the effluent by the end of the study (median influent pH at study end of 4.67 compared to a median effluent pH at study end of 4.73, p = 0.86; Figure S6), suggesting that hydroxyl groups on the carbon surface are gradually exhausted [62]. Furthermore, Pb is highly soluble in acidic, low-alkalinity waters [63] like those in cluster C. Characterization of particulate and dissolved Pb levels during profile sampling in a subset of homes in cluster C confirmed that 98% of influent Pb was in the dissolved form. Thus, the dominant removal mechanism in low pH waters appears to be through precipitation of influent dissolved Pb ions on the alkaline carbon surface or in the pore liquid.…”
Section: Influent Groundwater Phmentioning
confidence: 99%
“…Although the specific activation process and pre-treatment of the AC in the filter tested in this study is not known, the pH increased significantly in the effluent samples, with a greater increase at early time points (median influent pH at start-up of 5.23 compared to a median effluent pH at start-up of 9.13, p < 0.0005) and a gradual equilibration between the influent and the effluent by the end of the study (median influent pH at study end of 4.67 compared to a median effluent pH at study end of 4.73, p = 0.86; Figure S6), suggesting that hydroxyl groups on the carbon surface are gradually exhausted [62]. Furthermore, Pb is highly soluble in acidic, low-alkalinity waters [63] like those in cluster C. Characterization of particulate and dissolved Pb levels during profile sampling in a subset of homes in cluster C confirmed that 98% of influent Pb was in the dissolved form. Thus, the dominant removal mechanism in low pH waters appears to be through precipitation of influent dissolved Pb ions on the alkaline carbon surface or in the pore liquid.…”
Section: Influent Groundwater Phmentioning
confidence: 99%
“…Although Pb solubility modeling is based on a fundamental approach to simulate the total soluble Pb concentration in drinking water for a given water quality, very little advancement has been made in the drinking water field to make such models widely accessible to allow continued development, ease of evaluation, and a reproducible framework. Drinking water Pb solubility models are available pre‐programmed in commercial software (e.g., Water!Pro, Schott, 1998), have been developed in computer codes such as Fortran (e.g., Schock, 1980, 1981, 1989; Schock et al, 1996), or implemented using various software, including MINEQL+ (e.g., Dodrill & Edwards, 1995; Edwards et al, 1999) or PHREEQC (e.g., Jurgens et al, 2019). In addition, other platforms are readily available where Pb solubility models could be implemented, including MINTEQ and Visual MINTEQ (Gustaffson, 2015), the Geochemist's Workbench (Bethke, 2010), and Microsoft Excel (Crouch & Holler, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion from road salts poses particular risk to private wells and drinking water infrastructure (Pieper et al 2018). Corrosion from pipes in self-supplied groundwater in the USA contaminates drinking water with Pb, calcite, and apatite, where about 15% of wells tested were at risk of Pb dissolution, and highest Pb concentrations were found in California, Maryland, and Pennsylvania (Jurgens et al 2019). While Pb pipes are being phased out of use in the US and other developed nations, some drinking water infrastructure still relies on Pb pipes, and even plumbing systems without Pb pipes show calcite and apatite precipitates in pipes can leach Pb (Jurgens et al 2019).…”
Section: Identifying Risks Of Fss On Human Health Risks and Safe Drinking Watermentioning
confidence: 99%